(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
Water is the cause of diarrhea, hepatitis, typhoid, paratyphoid, and diarrheal diseases can cause it to come out. Looking back at history, many that epidemics of various infectious diseases spread in different countries we will witness. These are often associated with waterborne infections caused by pollution. In the following years, internal diseases are becoming more common. B is in it viruses play a big role. Jaundice, poliomyelitis and other diseases causative viruses live in water for a long time.